INTERNET OF THINGS UNTUK INFORMASI CUACA MENGGUNAKAN NODE MCU - Ahmad Pakhrul Islam; Lalu Puji Indra Kharisma; Muhammad Azmi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2022)
Weather is one of the natural factors that have both positive and negative effects on human life depending on how it is used and the influence of weather aspects on the work or activities carried out. Thus making weather information important things to know, especially for the food industry that uses sunlight for drying, as well as activities carried out outdoors. One way to find out the weather is to look at the weather forecast that has been provided on the site of a weather information service provider such as BMKG, but sometimes the information is intended for a large area, so there will be differences in the weather at certain locations. One way to overcome this is to create a tool that can read the weather in a local area, then it can be accessed via a website using the Internet Of Things (IOT) concept. This research was conducted using the waterfall method to produce a tool using an MCU Node that can read the weather in the local area, then sends the data to databased on a web server as well as a website page that can display weather information from a databased server where data is stored as a result of reading the weather. the tool. After the testing process, there are differences in the readings on the weather from the equipment placed in Anjani Village, Suralaga Sub-district with weather predictions for East Lombok Regency ranging from 1-5°C to read temperature, and 0-20%RH to read humidity. As for the results of reading the rain sensor there is no difference at all.